2019
DOI: 10.1016/j.atherosclerosis.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of elevated circulating fibroblast growth factor 21 levels with prevalent and incident metabolic syndrome: The Multi-Ethnic Study of Atherosclerosis

Abstract: Background and aims: Fibroblast growth factor 21 (FGF21) plays an important role in glucose and lipid metabolism. We have investigated the relationship of plasma FGF21 levels with both prevalent and incident metabolic syndrome (MetS) in participants from the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: 5783 participants from four major ethnic groups (non-Hispanic white, African American, Hispanic American, and Chinese American) were included in the cross-sectional analysis. Longitudinal analysis invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Given the different physiological states present in those with obesity, it is wise to consider that biological responses or treatment responses likely differ dependent on the metabolic state of the person. These analyses indicated that other factors may influence levels of FGF21 such differences between sexes or between racial and ethnic groups; however, larger studies have indicated that such interactions have not been significant and instead FGF21 was determined to be valuable as a biomarker for metabolic syndrome in multi-ethnic populations [ 20 , 21 ]. Thus, these findings from the EMBARC study support the association of FGF21 with MDD and provide further evidence that metabolic changes in MDD are worthy of further study as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the different physiological states present in those with obesity, it is wise to consider that biological responses or treatment responses likely differ dependent on the metabolic state of the person. These analyses indicated that other factors may influence levels of FGF21 such differences between sexes or between racial and ethnic groups; however, larger studies have indicated that such interactions have not been significant and instead FGF21 was determined to be valuable as a biomarker for metabolic syndrome in multi-ethnic populations [ 20 , 21 ]. Thus, these findings from the EMBARC study support the association of FGF21 with MDD and provide further evidence that metabolic changes in MDD are worthy of further study as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, clinical studies have shown that levels of circulating FGF21 are often elevated, notably in pathophysiological states, including T2DM [ 35 ], fatty liver diseases [ 36 , 37 ], and coronary heart diseases [ 38 ]. Moreover, elevated FGF21 level has recently emerged as an independent predictor for both the prevalence and incidence of MetS, regardless of age, gender, and race/ethnicity [ 39 ]. Likewise, habitually active individuals have lower circulating FGF21 concentration alongside better glucose tolerance and insulin sensitivity than the age- and sex-matched sedentary individuals [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ong et al found that FGF21 levels were higher in patients with metabolic syndrome compared to those without. 68 Similarly, Baek et al found that FGF21 levels were higher found in obese children and were correlated with Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), indicating FGF21 could be a predictive biomarker for obesity-induced insulin resistance. 69 Thus, FGF21 may still be a useful predictive marker of type 2 diabetes, but this may be specific to patients with pre-existing conditions associated with metabolic syndrome.…”
Section: Family History Of Type 2 Diabetes and Serum Fibroblast Growtmentioning
confidence: 95%
“…However, additional research has generally suggested that elevated serum FGF21 is associated with pre‐existing medical conditions. Ong et al found that FGF21 levels were higher in patients with metabolic syndrome compared to those without . Similarly, Baek et al found that FGF21 levels were higher found in obese children and were correlated with Homeostatic Model Assessment of Insulin Resistance (HOMA‐IR), indicating FGF21 could be a predictive biomarker for obesity‐induced insulin resistance .…”
Section: Relationship Between Family History Of Type 2 Diabetes and Smentioning
confidence: 97%